The Image of Knyaz Vladimir in Popular Literature (The Second Half of XIX Century) - Pozdniakov A. N. (Interactive science, 2020)
the article analyzes the literature published in the second half of the XIX century for popular reading, dedicated to the life and work of Prince Vladimir of Kiev. One of the main results of his activity was the adoption of Christianity in Russia. This had a profound impact on the political, social and cultural life of the country. Literature for popular reading formed in the minds of people the image of Prince Vladimir as an extraordinary person, a simple and at the same time a great man. He is shown as a statesman who transformed the country, laid the foundations of a new civilization, and simultaneously became a national hero.
Keywords: культура; христианство; язычество; Политика; culture; Christianity; mentality; Образ жизни; Politics; way of life; образ мыслей; paganism